Performance of female hedge fund managers - Garvert, Stacie (Kansas State University, 2008)
It is often argued that women have a tendency to be more risk averse than men. This thesis looks deeper into this sophisticated relationship between women, men and money, and investigates the gender differences among U.S. hedge fund managers. Prior research has considered the relationship between mutual fund performance and fund manager characteristics focusing on age, tenure, and level of education. However, none of these previous studies have looked in depth at the hedge fund arena. I hypothesize that female fund managers take less risk and follow less extreme investment styles that remain more constant over time. This suggests that less trading by female managers takes place with lower portfolio turnover, and results in superior net returns. I expected female money managers to be less overconfident and therefore would then trade less. Despite the similarities between female and male managers, I found evidence supporting my hypothesis that gender does indeed influence the decision making process for both investors and the hedge fund management companies.
Keywords: Hedge fund performance; female managers; Business Administration, General (0310); Economics, Finance (0508); Economics, General (0501)